2021
DOI: 10.1108/ecam-09-2020-0741
|View full text |Cite
|
Sign up to set email alerts
|

Total factor productivity growth and its decomposition in the Chinese construction industry since China's accession to the World Trade Organization

Abstract: PurposeSince China's accession of the World Trade Organization (WTO), its construction industry has attained unprecedented growth. However, for the sources of this enormous growth, a controversy regarding the total factor productivity growth (TFPG) still remains in production practice and extant studies. In view of this, the purpose of this paper is to measure TFPG and to explore its sources in the industry post-WTO accession.Design/methodology/approachThis study presents an innovative source analysis of TFPG.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…At the construction industry level, using a trans log production function and the Kumbhakar et al (2000) decomposition method, Wang et al (2021) found that TI and AEI have a significant positive impact in China, while TEI has contribute to an adverse effect. However, a previous result by Chancellor andLu (2016) using FPI andthe O'Donnell (2012) decomposition method indicates that China's construction industry is mainly driven by scale efficiency instead of TI.…”
Section: Literature Review Review Of Recent Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…At the construction industry level, using a trans log production function and the Kumbhakar et al (2000) decomposition method, Wang et al (2021) found that TI and AEI have a significant positive impact in China, while TEI has contribute to an adverse effect. However, a previous result by Chancellor andLu (2016) using FPI andthe O'Donnell (2012) decomposition method indicates that China's construction industry is mainly driven by scale efficiency instead of TI.…”
Section: Literature Review Review Of Recent Literaturementioning
confidence: 99%
“…At the construction industry level, using a trans log production function and the Kumbhakar et al. (2000) decomposition method, Wang et al. (2021) found that TI and AEI have a significant positive impact in China, while TEI has contribute to an adverse effect.…”
Section: Literature Reviewmentioning
confidence: 99%